Value of stability in photovoltaic life cycles - Peters, Ian Marius; Sinha, Parikhit (Conference Record of the IEEE Photovoltaic Specialists Conference, 2021)
PV module stability, in terms of reduced degradation rate and increased lifetime, provides an important lever for reducing the levelized cost of energy and life cycle environmental impacts of PV systems. Adapting an earlier value of efficiency methodology, the PV module cost per watt entitlement for a 30-year system lifetime is estimated to be 0.0125/W per 0.1% reduction in annual degradation rate, based on LCOE calculations. From an environmental perspective, the life cycle carbon footprint of a ground-mount PV system in a high solar resource location can be reduced by 0.3-1.0 g CO2-eq/kWh per 0.1% reduction in annual degradation rate. Increasing average PV module lifetime from 30 to 50 years will further increase these benefits, would reduce annual replacements by 40% and would result in net deferment of 62% of the projected module decommissioning through 2050 for PV modules installed in 2020. Increasing lifetime of state-of-the-art PV modules by 20 years to harvest the value of stability fully will require reducing PV module degradation rates to 0.2%/yr.
CRIS-Team Scopus Importer:2022-06-05